Digital Government: A Primer and Professional Perspectives. Issue 1 (March 2015) - Katsonis, Maria; Botros, Andrew
<x xml:space="preserve">Abstract</x> Digital technology is a critical enabler of public administration reforms. It can improve the efficiency and productivity of government agencies and allow citizens to transact with government anytime, anywhere. It can also deepen the democratic process, empowering citizens to participate in policy formulation. In this article Andrew Botros, the director of Expressive Engineering, and Maria Katsonis, from the Department of Premier and Cabinet (Victoria), explore the challenges of the digital world for the public sector. Katsonis presents a primer on digital government tracing its evolution from the e‐government movement of the 1990s to Government 2.0 in the 2000s to today's digital‐by‐default agenda. As technology and its role in public sector reform have progressed, so too have the governance, cultural, and leadership challenges deepened. Botros examines NSW approach to open innovation with the Premier's Innovation Initiative in NSW, the state's open data experience, and Transport for NSW and its management of public transport data. He argues NSW's approach involves a significant innovation trade‐off, requiring fresh thinking in digital‐era collaboration.